2013
DOI: 10.1007/s10157-013-0916-3
|View full text |Cite
|
Sign up to set email alerts
|

CD147/basigin reflects renal dysfunction in patients with acute kidney injury

Abstract: Background Acute tubular necrosis (ATN) describes a form of intrinsic acute kidney injury (AKI) that results from persistent hypoperfusion and subsequent activation of the immune system. A glycosylated transmembrane protein, CD147/basigin, is involved in the pathogenesis of renal ischemia and fibrosis. The present study investigated whether CD147 can reflect pathological features and renal dysfunction in patients with AKI. Methods Plasma and spot urine samples were collected from 24 patients (12 controls and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…CD147 is well established as an MMP inducer (57-59) and has been shown to have multifunctional roles in many progressive diseases and in animal models of disease (28)(29)(30)(31), including, cardiovascular disease, Alzheimer's and more recently as an entry route into cells for SARs-CoV-2 (COVID 19) (60-62). Its involvement in CKD has been well described (32,33) and in the supplementary data (Fig. 10) we show its changing expression in a mouse model of CKD.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…CD147 is well established as an MMP inducer (57-59) and has been shown to have multifunctional roles in many progressive diseases and in animal models of disease (28)(29)(30)(31), including, cardiovascular disease, Alzheimer's and more recently as an entry route into cells for SARs-CoV-2 (COVID 19) (60-62). Its involvement in CKD has been well described (32,33) and in the supplementary data (Fig. 10) we show its changing expression in a mouse model of CKD.…”
Section: Discussionsupporting
confidence: 65%
“…In chronic kidney models, Bsg +/+ mice that had undergone unilateral ureteral obstruction had increased kidney interstitial fibrosis compared to bsg-/-mice with increased MMP activation, macrophage infiltration and upregulation of αSMA and hyaluronan by fibroblasts (31). Regardless of the primary underlying kidney disease or its pathogenesis in CKD patients, there is also a significant relationship between the degree of proteinuria and urinary CD147 (32). In addition it has been suggested that in CKD there may be a "molecular circuit" involving CD147, MMPs and transforming growth factor-β and that this may be involved in the pathogenesis of progressive fibrosis through hyaluronan production (33).…”
Section: Introductionmentioning
confidence: 99%
“…189 In biopsy specimens of patients with acute tubular necrosis, basigin expression was found on inflammatory cells in the interstitium and was absent in damaged tubules. 190 Moreover, it was found in patients after abdominal aortic aneurysm surgery that serum and urine levels of basigin on postoperative day 1 was higher in patients who developed AKI than in those who did not and had a similar profile as that of urinary L-FABP. 190 Intercellular adhesion molecule-1 is a 58-kDa cellsurface glycoprotein of the Ig superfamily expressed mainly on endothelial and some immune cells.…”
Section: Q30mentioning
confidence: 98%
“…190 Moreover, it was found in patients after abdominal aortic aneurysm surgery that serum and urine levels of basigin on postoperative day 1 was higher in patients who developed AKI than in those who did not and had a similar profile as that of urinary L-FABP. 190 Intercellular adhesion molecule-1 is a 58-kDa cellsurface glycoprotein of the Ig superfamily expressed mainly on endothelial and some immune cells. It functions as an adhesion molecule on endothelial cells that upon activation by the cytokines IL-1 and TNF-α or reactive oxygen species allow attachment of circulating neutrophils and leukocytes via their β 2 integrin receptors LFA Q33 -1 and Mac-1.…”
Section: Q30mentioning
confidence: 98%
“…This mechanism has been proven to take place in numerous in vivo experiments in sepsis-induced AKI, bronchial asthma, lipopolysaccharide-induced lung injury and collagen-induced arthritis. [7] There are no reports on CD147 in the context of renal graft IRI, but its role in spreading in ammation can be deduced from the native kidney IRI model. Elevated CD147 concentrations have been shown to be present in acute kidney injury.…”
Section: Emmprin/cd147mentioning
confidence: 99%